2016
DOI: 10.1080/10286020.2016.1171758
|View full text |Cite
|
Sign up to set email alerts
|

Polygonumnolides C1-C4; minor dianthrone glycosides from the roots of Polygonum multiflorum Thunb

Abstract: Four new dianthrone glycosides, named polygonumnolides C1-C4 (1-4), were isolated from the dried roots of Polygonum multiflorum Thunb, together with two known emodin dianthrones (5-6). Their hepatotoxicities were evaluated against L-02 cell lines. Compounds 1-4 showed weak hepatotoxicity against L-02 cell lines with IC50 values of 313.05, 205.20, 294.20, and 207.35 μM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Actually, several novel dianthrone glycosides from PM were elucidated by the conventional phytochemistry methods 4 years later (Yang J. B. et al, 2016 ; Yang et al, 2017a , b ), which confirmed the existence of dianthrone glycosides in PM. Compared with traditional Q-TOF mass spectrometry, UPLC-LTQ-Orbitrap-MS n provides superior resolution and mass accuracy; meanwhile, with the MS n function, the Orbitrap technology can achieve 10 levels of MS analysis capability (Lin et al, 2015d ).…”
Section: Chemical Analysis Of Pmmentioning
confidence: 92%
See 1 more Smart Citation
“…Actually, several novel dianthrone glycosides from PM were elucidated by the conventional phytochemistry methods 4 years later (Yang J. B. et al, 2016 ; Yang et al, 2017a , b ), which confirmed the existence of dianthrone glycosides in PM. Compared with traditional Q-TOF mass spectrometry, UPLC-LTQ-Orbitrap-MS n provides superior resolution and mass accuracy; meanwhile, with the MS n function, the Orbitrap technology can achieve 10 levels of MS analysis capability (Lin et al, 2015d ).…”
Section: Chemical Analysis Of Pmmentioning
confidence: 92%
“…Besides Lin et al ( 2015a ) summarized 103 chemical compounds of PM, one new type agents were discovered by our group (Yang J. B. et al, 2016 ; Yang et al, 2017a , b ), more than 30 novel dianthrone glycosides were elucidated unambiguously by spectroscopic analysis. In addition, the toxicities of parts compounds were evaluated against L-02 cell lines and KB tumor cell lines, and the results indicated that these constituents showed moderate hepatotoxicities.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 94%
“…multiflorum (common names: Polygonum multiflorum Thunb 1 , Polygoni Multiflora Radix 2 , Fallopia multiflora , Heshouwu 3 , fleeceflower root 4 , 5 , Polygoni multiflori 6 , and foti root 7 ) is among the most frequently used medicinal plants in China. The main components of this plant are flavonoids 1 , 8 – 11 , quinones, and anthrones 12 , which are used as ingredients in various medicines. The major quinone constituents of P .…”
Section: Introductionmentioning
confidence: 99%
“…Previous chemical investigations revealed that the plant P. multiflorum contains stilbenes, phenolic acids, flavonoids and anthraquinones etc. . These multiple‐bioactive constituents, contributed to the plant, become an important herbal medicine source.…”
Section: Introductionmentioning
confidence: 99%